If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 2 + -3a = -7 + a + -11 Combine like terms: -6 + 2 = -4 -4 + -3a = -7 + a + -11 Reorder the terms: -4 + -3a = -7 + -11 + a Combine like terms: -7 + -11 = -18 -4 + -3a = -18 + a Solving -4 + -3a = -18 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. -4 + -3a + -1a = -18 + a + -1a Combine like terms: -3a + -1a = -4a -4 + -4a = -18 + a + -1a Combine like terms: a + -1a = 0 -4 + -4a = -18 + 0 -4 + -4a = -18 Add '4' to each side of the equation. -4 + 4 + -4a = -18 + 4 Combine like terms: -4 + 4 = 0 0 + -4a = -18 + 4 -4a = -18 + 4 Combine like terms: -18 + 4 = -14 -4a = -14 Divide each side by '-4'. a = 3.5 Simplifying a = 3.5
| C=d-1 | | 20-(x+5)=6x-6 | | 4d(d+2)-2d=3(2+d) | | 3+5x=9+3x | | 1/2(2x-4)=3x+5/6 | | [3v-2]/5=4 | | 9y-5-6y+1=0 | | 35-7x=9(3x+3) | | (4x^2+3)(x-4)(x+4)=0 | | 8y+13=5y-5 | | (y+.33)(y-.33)= | | [1-6n]+3=46 | | 5x^2-6x+5= | | 0.1(x+250)=5,000 | | 8x^5+26x^3-24x=0 | | x=1056-.1x | | 7(z-5)+1=2-3(2z-1) | | 2x+6x-14=22 | | [4x+4]=28 | | 12+x=-3x(4-x) | | 6(2x-5)=12 | | -118-3x=77+12x | | 12x+x=-3x(4-x) | | [-7x+4]=18 | | 2(6x+2)=-(2x-10) | | C=3ab | | (x+0.2)(x-0.2)= | | -11a-17a+11a+10a+-2a=18 | | 4x-37=x+35 | | 1/2+3/2=3 | | C=3pieab | | 20x-16=4x+ |